2020
DOI: 10.12669/pjms.36.5.2150
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of serum levels of Vitamin D3 with serum parathormone in nursing mothers and infants 1-6 months’ age from South Punjab, Pakistan

Abstract: Background and Objective: Parathormone (PTH) and serum Vitamin D3 (VD3) share a complex interplay where increased VD3 leads to a negative response on parathormone level. Our objective was to determine the correlation of parathormone (PTH) and Vitamin D3 (VD3) levels in nursing mothers and infants 1-6 months’ age from South Punjab, Pakistan. Methods: This study is a secondary data analysis of previously conducted cross sectional study which was conducted at the Department of Pediatric Medicine, Nishtar Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…In our study, we found that among euglycemic obese women, though PTH and calcium levels were negatively correlated significantly ( r = −0.267, P = 0.008), their individual negative correlation with vitamin D was not significant. Such noncustomary relation between vitamin D, PTH, and calcium is also reported among Pakistani women in other studies [ 13 , 14 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In our study, we found that among euglycemic obese women, though PTH and calcium levels were negatively correlated significantly ( r = −0.267, P = 0.008), their individual negative correlation with vitamin D was not significant. Such noncustomary relation between vitamin D, PTH, and calcium is also reported among Pakistani women in other studies [ 13 , 14 ].…”
Section: Discussionsupporting
confidence: 81%
“…Vitamin D deficiency and increased concentration of PTH [ 11 ] as well as calcium [ 12 ] are implicated in the augmented risk of diabetes. This is especially relevant to Pakistani subjects as they are reported to have low vitamin D, high PTH, and increased calcium level with nonconventional relation between vitamin D, PTH, and calcium [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%